Flow Field Measurement Of Fish And Development Of Fish Like Underwater Robot - Soh, Ling Xin (Universiti Sains Malaysia, 2018)
Biomimetic systems had been an advancement to apply in robotic field. The development of the underwater robot requires the study of locomotion and flow around the swimming fish. Therefore, for the development of an aquatic robotic necessitate the investigation of live fish locomotion since it's manoeuvrability and efficiency is excellent. The work presented in this thesis aimed to visualise flow of mechanical fish tail which is designed and fabricated for having the mechanism which similar locomotion as alive fish. Firstly, the swimming Gold Gourami and Opaline Gourami fishes are visualized, especially the vortex shedding produced when fishes propelled. Next, the design and fabrication of water channel has been done before hand to undergo the flow visualisation of Gourami fishes and mechanical fish tail. The experiment will be conducted in two stages where the first stage will be the observation of tail kinematic and visualization flow behind tail of Gourami fishes under water-still condition. Then, the design and fabricate of the mechanical fish tail extract from the data of visualization alive fishes will be done. Thus, the second stage will be the flow visualization of mechanical fish tail. The method of visualization will be Particle Image Velocimetry (PIV). The water flow in water channel is laminar with velocity of 0.28m/s to undergoes the experiment. Body of Gourami fish will bend into S-shaped for sudden speed up and C-shaped for steady swimming. The steady swimming of Gourami fishes shows the vortex chain produced behind the fish tail. The higher the frequency of flapping fish tail will increase the number of vortices produced by the Gourami fish. Hence, the vortex chain would be longer. The vortex chain pattern produced by flapping amplitude of 20 ° was having the highest similarity with Gourami fish compared to 40 ° and 60 °.